2019
DOI: 10.1007/s00204-019-02442-5
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring bisphenol F in plants used in traditional medicine

Abstract: Bisphenol F (BPF, 4-[(4-hydroxyphenyl)methyl]phenol) is a bisphenol that is structurally similar to bisphenol A (BPA). In response to consumer concern towards BPA, industry has started to substitute BPA for BPF and other bisphenol analogues in the production of epoxy resins and coatings for various applications. In 2016, it was reported that commercially sold mustard contained naturally occurring BPF. Here, the existing literature was reviewed to investigate whether other natural sources of BPF among edible pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Higher BPA levels in younger ages have also been observed in several other studies [ 62 , 63 , 64 ]. BPA is commonly used in various products for everyday use, including water-pipes, electronic equipment, paper, or toys [ 65 ]. A Greek child cohort study showed that BPA was associated with exposure to plastics and personal care products.…”
Section: Discussionmentioning
confidence: 99%
“…Higher BPA levels in younger ages have also been observed in several other studies [ 62 , 63 , 64 ]. BPA is commonly used in various products for everyday use, including water-pipes, electronic equipment, paper, or toys [ 65 ]. A Greek child cohort study showed that BPA was associated with exposure to plastics and personal care products.…”
Section: Discussionmentioning
confidence: 99%
“…The most common bisphenols found in polluted waters are bisphenol A (BPA), an organic molecule often used in plastics and resins fabrication, 135 and bisphenol F (BPF), an analogue molecule used as a substitute for BPA. 136 Extensive monitoring of BPA in various environmental media has been conducted over the last years. In 2009, a statistical analysis considering 89 investigations concluded that the median environmental BPA concentrations for fresh surface water for North America and Europe were 0.081 and 0.01 μg L −1 , respectively.…”
Section: Bisphenol Compoundsmentioning
confidence: 99%
“…A study ) on PAHs has shown a detection rate of 100% in 109 samples of TCM such as honeysuckle, with a maximum exceeding rate of 12.5%. In a review (Huang et al 2019) on bisphenol F (BPF), the highest content was found in Gastrodia elata with 69.5 mg/kg.…”
Section: Other Kinds Of Edcs In Tcmmentioning
confidence: 99%